1971
DOI: 10.1063/1.1676742
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Liquids and the Glass Transition. III. Secondary Relaxations in Aliphatic Alcohols and Other Nonrigid Molecules

Abstract: Theory of relaxation in viscous liquids and glasses J. Chem. Phys. 81, 954 (1984); 10.1063/1.447697Viscous liquids and the glass transition. VI. Relaxations in simple molecule glasses in the 4-77 K range CONCLUSIONS ACKNOWLEDGMENTThe efg tensor resulting from a spanning of the T?g or the Eg subspace by real coefficients displays, remarkably, a constant electric quadrupole splitting and a variety of values of V .. and 7/. None of this information is present in the usual M ossbauer spectrum. Magnetic perturbatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
183
1
8

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(197 citation statements)
references
References 17 publications
5
183
1
8
Order By: Relevance
“…The difference among the different existing β processes is, usually, neglected in theoretical modeling, even though their relaxation times can differ for several orders of magnitude. The 2RSB phase might, then, describe systems where slow β (as, e.g., Johari-Goldstein processes [41]) and fast β (e.g., collisions) processes are well separated. This is, indeed, what happens in many glasses where, at a temperature a few degrees below the glass transition temperature, Johari-Goldstein-like β relaxation occurs on time scales up to the order of the millisecond.…”
Section: Resultsmentioning
confidence: 99%
“…The difference among the different existing β processes is, usually, neglected in theoretical modeling, even though their relaxation times can differ for several orders of magnitude. The 2RSB phase might, then, describe systems where slow β (as, e.g., Johari-Goldstein processes [41]) and fast β (e.g., collisions) processes are well separated. This is, indeed, what happens in many glasses where, at a temperature a few degrees below the glass transition temperature, Johari-Goldstein-like β relaxation occurs on time scales up to the order of the millisecond.…”
Section: Resultsmentioning
confidence: 99%
“…But, as the dipole moment of o-terphenyl is extremely small, the relaxation strength due to these fast motions in its glassy and ultraviscous liquid states is extremely small and could not be measured accurately enough to investigate the effect observed earlier. 4 In contrast, diethyl phthalate has a relatively large dipole moment and an earlier study had shown that its dielectric loss peak is sufficiently high in the glassy state 5 and therefore may allow comparison of the relaxation strength data with the C p and entropy data. When this work was being done, Pawlus et al 6 have reported the ␣-relaxation spectra of diethyl phthalate over a broad temperature range in the ultraviscous liquid state and the secondary or faster relaxation spectra over a relatively narrow temperature range in the glassy and ultraviscous liquid state.…”
Section: Introductionmentioning
confidence: 99%
“…14 A previous study had already shown a ␤-relaxation peak in its glassy state. 5 One of the characteristic features of the ␤ relaxation is that its relaxation strength increases with increase in the temperature T. 4,5,18 This means that as the number of molecules contributing to the availability of distinct configurations increases with increase in T, C p,exc and S exc and any contribution to volume should increase, and hence one would expect that the increase in the ␤-relaxation strength may be at least qualitatively related to C p,exc and S exc and possibly to free volume. Bartoš and co-workers [19][20][21][22][23][24][25] have studied a series of glasses, both molecular and polymeric and have found that as T is increased, the hole volume V h in the structures of the glass and ultraviscous liquid also increases slowly.…”
Section: Introductionmentioning
confidence: 99%
“…27,40 Characteristics of the JG relaxation have been recently reviewed. 1,2 Briefly, ͑i͒ the ␣-relaxation process appears to evolve from it at a temperature where its relaxation rate is in the microsecond range, 16,41 a temperature termed as the Donth temperature ͑for the merging of the ␣-and ␤-relaxation processes͒, ͑ii͒ the height of the dielectric relaxation peak Љ m,JG and its relaxation strength ⌬ JG decreases on structural relaxation or aging of a glass, [8][9][10]12,24,28 ͑iii͒ its spectral half width, which is much larger than that of the ␣-relaxation process, increases with a decrease in the temperature, [6][7][8][9][10][12][13][14][15]23,26,29 ͑iv͒ its relaxation rate follows an Arrhenius temperature dependence at temperatures [6][7][8][9][13][14][15][16]18,19,25,[29][30][31]42 far below the Donth temperature, with an activation energy and preexponent compatible with that for hindered molecular reorientation, ͑v͒ the ⌬ JG against temperature plot shows a feature similar to that of enthalpy relaxation on heating, 17,18,26 and an elbow-shape change in the slope occurs a...…”
Section: Introductionmentioning
confidence: 99%